Reduced mitochondrial DNA content associates with poor prognosis of prostate cancer in African American men. - Shahriar Koochekpour (PLoS ONE, 2013)
Reduction or depletion of mitochondrial DNA (mtDNA) has been associated with cancer progression. Although imbalanced mtDNA content is known to occur in prostate cancer, differences in mtDNA content between African American (AA) and Caucasian American (CA) men are not defined. We provide the first evidence that tumors in AA men possess reduced level of mtDNA compared to CA men. The median tumor mtDNA content was reduced in AA men. mtDNA content was also reduced in normal prostate tissues of AA men compared to CA men, suggesting a possible predisposition to cancer in AA men. mtDNA content was also reduced in benign prostatic hyperplasia (BPH) tissue from AA men. Tumor and BPH tissues from patients ≥ 60 years of age possess reduced mtDNA content compared to patients <60 years of age. In addition, mtDNA content was higher in normal tissues from patients with malignant T3 stage disease compared to patients with T2 stage disease. mtDNA levels in matched normal prostate tissues were nearly doubled in Gleason grade of >7 compared to ≤ 7, whereas reduced mtDNA content was observed in tumors of Gleason grade >7 compared to ≤ 7. Together, our data suggest that AA men possess lower mtDNA levels in normal and tumor tissues compared to CA men, which could contribute to higher risk and more aggressive prostate cancer in AA men.